Pengaruh Latihan Ekstremitas Atas Terhadap Kekuatan Otot Pada Pasien Penyakit Paru Obstruktif Kronis (PPOK) Di Puskesmas Siatas Barita - Lumbantobing, Dikki Samuel; Sembiring, Hizkianta (Indonesian Trust Nursing Journal, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic respiratory disorder that not only causes airflow limitation but also leads to systemic impacts, including upper extremity muscle weakness. This condition may interfere with daily activities and reduce patients’ quality of life. To determine the effect of upper extremity exercises on muscle strength among COPD patients at Siatas Barita Public Health Center. This study used a One Group Pretest–Posttest Design with 8 respondents selected through total sampling. Muscle strength was assessed using Manual Muscle Testing (MMT) before and after upper extremity exercise intervention. Data were analyzed using the Wilcoxon Signed Rank Test due to non-normal distribution. There was a significant improvement in upper extremity muscle strength after the intervention, with a p-value = 0.018 (p < 0.05). The mean MMT score increased from 2.875 in the pre-test to 4.000 in the post-test, indicating a meaningful enhancement in muscle strength. Upper extremity exercise is effective in improving muscle strength in COPD patients and can be used as a non-pharmacological intervention to support physical function. Further studies with larger samples and more comprehensive instruments are recommended.